Changes in Gastric Microbiota during Gastric Carcinogenesis - Sun-Young Lee (The Korean Journal of Helicobacter and Upper Gastrointestinal Research, 2018)
After World War II, the incidence of gastric cancer decreased rapidly in most of the developed countries; however, it remained high in countries where secondary prevention of gastric cancer is practiced without primary prevention (Helicobacter pylori eradication). In such countries, changes in gastric microbiota contribute to gastric carcinogenesis, and the composition of gastric microbiota is mainly determined by the status of H. pylori infection. In non-infected individuals with no history of H. pylori infection, gastric microbiota includes various bacteria, creating ideal microbial diversity. Because it is difficult for most bacteria to proliferate in an acidic environment in stomach, only few bacteria are present in non-infected individuals. Conversely, microbial dysbiosis with H. pylori predominance is often observed in infected individuals with unimpaired gastric secretory ability, because other bacteria cannot survive at low intragastric pH. Such microbial dysbiosis may rapidly lead to gastric carcinogenesis, resulting in diffuse-type gastric cancer. It is more frequent in young patients with unimpaired gastric secretory ability than in elderly patients with gastric atrophy and metaplasia. Lastly, bacteria producing carcinogenic N-nitrosamine compounds are often detected in individuals with past or chronic H. pylori infection, because of the loss of gastric secretory ability. Such an unideal microbial diversity observed at high intragastric pH may slowly lead to gastric carcinogenesis, in turn resulting in gastric adenoma or intestinal-type gastric cancer. To prevent gastric carcinogenesis, changes in the composition of gastric microbiota should be studied in conjunction with intragastric acidity, which depends on the status of H. pylori infection.